THE ROLE OF POSITIVE EMOTIONS IN MEDIATING THE EFFECT OF FLASH SALES AND HEDONIC SHOPPING ON ONLINE IMPULSE BUYING (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
One of the widely used marketing tactics in e-commerce is flash sales, which offer significant discounts for a limited period. This study aims to analyze the effect of flash sale on positive emotions, the effect of hedonic shopping on positive emotions, the effect of flash sale on online impulse buying, the effect of hedonic shopping on online impulse buying, the effect of positive emotions on online impulse buying, the role of positive emotions in mediating the effect of flash sale on impulse buying, and the role of positive emotions in mediating the effect of hedonic shopping on impulse buying. The sample in this study consists of 123 respondents. Data analysis techniques were conducted using SmartPLS. The results indicate that flash sales and hedonic shopping influence positive emotions, and that both flash sales and hedonic shopping influence impulse buying. Moreover, positive emotions affect impulse buying and mediate the relationship between flash sales and impulse buying, as well as between hedonic shopping and impulse buying. JEL: D91, M31.